ELECTRICAL IMPEDANCE TOMOGRAPHY HARDWARE SYSTEM BASED ON LOW POWER DIGITAL SIGNAL PROCESSOR - Olchowy, Daniel (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
Article contains description of the measurement system electrical impedance tomography solutions based on digital signal processor with low power consumption.